ZIF‑8 membrane: the synthesis technique and nanofiltration application - Dayang Norafizan, Awang Chee; Farhana, Aziz; Mohamed Afizal, Mohamed Amin; Ahmad Fauzi, Ismail (Qatar University and Springer Nature Switzerland AG, 2022)
Membrane technology for water treatment is growing due to the increased demand for clean water and the stringent standard for water quality. Nanofiltration (NF) is widely used in membranes for water treatment due to lower energy consumption and higher flux rates. The application was not limited to only water treatment, yet NF showed excellent potential for solvent nanofiltration application. The utilization of MOF materials for the preparation of NF membranes to produce composite membranes has attracted more attention among researchers due to the advantages offered by the material. Zeolitic imidazolate framework-8 (ZIF-8) membrane has been considered a promising MOF membrane with its capabilities and promising per-formance due to the small aperture size of the compounds and the stability towards harsh chemical condition. The purpose of this review is to present the synthesis approaches on the preparation of ZIF-8 membranes and the application of ZIF-8 membrane for NF application. The challenges and prospects of ZIF-8 membranes are also discussed to further stimulate the development and the application of ZIF-8 membrane for NF.